Molecular Identification, GC-MS Analysis of Bioactive Compounds and Antimicrobial Activity of Thermophilic Bacteria Derived from West Sumatra Hot-Spring Indonesia - Zona Octarya; Titania Tjandrawati Nugroho; Yuana Nurulita; Saryono (HAYATI Journal of Biosciences, 2022)
Thermophilic bacteria are a source of bioactive compounds that have many benefits for human life. One of them is as a source of antimicrobials. This research aimed to identify and characterize the promising thermophilic bacterial isolates by analyzing bioactive compounds and their potential as antimicrobial agents. Thermophilic bacteria with the code LBKURCC were taken from the collection of the Biochemistry Laboratory of the University of Riau. Forty-four purified strains of thermophilic bacteria were tested for antimicrobial ability. These thermophilic bacteria were taken from hot springs located in the Sumatra provinces of West Sumatra and Riau. Strain LBKURCC218 isolated from Rimbo Panti hot springs in West Sumatra was chosen to further investigate antimicrobials production. Isolates of hot spring bacteria that produced the highest antimicrobial were identified by comparing the similarity of the 16S rRNA gene sequences. BLAST result and phylogenetic tree showed that the selected thermophilic bacterial strain was similar to Bacillus paramicoides with the similarity index of 99.93%. Analysis of bioactive compounds of the ethyl acetate extract of liquid cultures of B. paramycoides LBKURCC218 showed the best producer of antimicrobial compounds compared to other isolates. The most identified compounds from the ethyl acetate extract were Dodecanoic acid, representing 23.62% of the total compounds, followed by 11-Dodecanoic acid at 17.84%. Ethyl acetate extract of B. paramycoides LBKURCC218 has a high inhibition zone against Escherichia coli, Staphylococcus aureus, and Candida albicans.